2017
DOI: 10.1016/j.comgeo.2016.05.001
|View full text |Cite
|
Sign up to set email alerts
|

An algorithm for the maximum weight independent set problem on outerstring graphs

Abstract: Outerstring graphs are the intersection graphs of curves that lie inside a disk such that each curve intersects the boundary of the disk. Outerstring graphs are among the most general classes of intersection graphs studied. To date, no polynomial time algorithm is known for any of the classical graph optimization problems on outerstring graphs; in fact, most are NP-hard. It is known that there is an intersection model for any outerstring graph that consists of polygonal arcs attached to a circle. However, this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 21 publications
0
31
0
Order By: Relevance
“…If all points are on the boundary, then it is easy to represent each rectangle as a string (i.e., a Jordan curve) such that all strings have a point on the infinite face and two strings intersect if and only if not both rectangles should be taken; see Figure 2. This class of graphs is known as the outer-string graphs for which it is known that maximum-weight independent set is solvable in O(N 3 ) time, where N denotes the number of segments in a geometric representation of the input graph [8]. As such, BARP is solvable in O(n 9 ) time, but this is rather slow.…”
Section: Boundary-anchored Rectanglesmentioning
confidence: 99%
“…If all points are on the boundary, then it is easy to represent each rectangle as a string (i.e., a Jordan curve) such that all strings have a point on the infinite face and two strings intersect if and only if not both rectangles should be taken; see Figure 2. This class of graphs is known as the outer-string graphs for which it is known that maximum-weight independent set is solvable in O(N 3 ) time, where N denotes the number of segments in a geometric representation of the input graph [8]. As such, BARP is solvable in O(n 9 ) time, but this is rather slow.…”
Section: Boundary-anchored Rectanglesmentioning
confidence: 99%
“…Let R be a geometric representation of Γ(G), where C is represented as a simple polygon P , and each curve is represented as a simple polygonal chain inside P such that one of its endpoints coincides with a distinct vertex of P . Keil et al [8] showed that given a geometric representation R of G, one can compute a maximum weight independent set of G in O(s 3 ) time, where s is the number of line segments in R. [8] observed that any maximum weight independent set of strings can be triangulated to create a triangulation P t of P , as shown in Figure 7(c). They used this idea to design a dynamic programming algorithm, as follows.…”
Section: Computing Subsuming Polygonsmentioning
confidence: 99%
“…For a fixed triple i, j and k, we first compute OPT(I k ) and store the value in a table T , and will then do one look-up when computing the corresponding table entry of S[i, j]. To this end, we first note that index j is irrelevant for computing OPT(I k ) because for a fixed i and k, the set of L-shapes is the same for all k < j ≤ n. Therefore, for all pairs 1 ≤ i < k < n, we compute OPT(I k ) using the algorithm of Keil et al [23] and store it in T [i, k]. Since their algorithm takes O(n 3 ) and there are O(n 2 ) entries for T , the preprocessing step takes O(n 5 ) overall time.…”
Section: A (4 · Log Opt)-approximation Algorithmmentioning
confidence: 99%
“…To apply our algorithm, we now use the "weighted" median of the L-shapes in OPT[i, j]. Moreover, the algorithm of Keil et al [23] for the MIS problem on outerstring graphs works for weighted outerstring graphs as well. Finally, we can still compute the optimal solution for the weighted MIS problem when OPT[i, j] ≤ 4 for all 1 ≤ i < j ≤ j.…”
Section: A (4 · Log Opt)-approximation Algorithmmentioning
confidence: 99%